Stability Analysis and Traveling Wave Solutions of the Dynamic Model of Bird Flu Transmission in Poultry–Human Interaction - Dilla, Rahma; Putri, Arrival Rince; Alfiany, Noverina; Syafwan, Mahdhivan (Jurnal Matematika UNAND, 2025)
This study analyzes the stability of a mathematical model of avian influenza virus spread in poultry-human interaction population. The analysis was conducted to see the dynamics of the spread of avian influenza virus. From the model, the equilibrium points and basic reproduction numbers associated with the stability of the system are obtained. The results obtained show that stability depends on the basic reproduction number. Numerical simulations were carried out using Maple and gave the result that the infection rate is low and the system reaches a stable state where the infection does not disappear but does not spread significantly.